Studi Kasus Dampak Perundungan Verbal Pada Siswa SMAN 2 KS Cilegon: Case Study: The Impact of Verbal Bullying on Students at SMA Negeri 2 KS Cilegon - Melawati, Ayu; Indrawati; Atikah, Cucu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
This qualitative case study explores the impact of verbal bullying on students at SMA Negeri 2 Kota Cilegon (SMA 2 KS Cilegon). Verbal bullying, in the form of teasing, humiliation, derogatory remarks, disruptions, name-calling, sarcasm, insults, mockery, intimidation, and the spread of unverified rumors, has become a serious issue in the school environment. The research focuses on one bullying victim at SMA 2 KS Cilegon who is currently receiving attention from the Guidance and Counseling (BK) teacher due to verbal bullying. The findings reveal severe psychological impacts on the victim, including a significant decrease in self-esteem, increased anxiety, sleep disturbances, loss of interest in previously enjoyed activities, and excessive anxiety symptoms. The role of the BK teacher in providing emotional support, counseling services, and guidance to the victim is crucial. However, the BK teacher faces challenges, such as difficulties in identifying the bullies and collecting strong evidence. The school's response to bullying issues is also a critical factor in case management. This study provides in-depth insights into the psychological impact of verbal bullying on students and the vital role of BK teachers in aiding victims. The implications of this research underscore the importance of awareness and concrete steps to prevent verbal bullying and create a safe and supportive school environment for all students. Abstrak Penelitian ini merupakan studi kasus kualitatif yang mengeksplorasi dampak perundungan verbal terhadap siswa di SMA Negeri 2 Kota Cilegon (SMA 2 KS Cilegon). Perundungan verbal, dalam bentuk menyindir, mempermalukan, merendahkan, mengganggu, memberi panggilan nama lain (name-calling), sarkasme, mencela/mengejek, mengintimidasi, memaki, dan menyebarkan berita yang belum jelas kebenarannya, telah menjadi isu serius di lingkungan sekolah. Fokus penelitian ini adalah pada satu korban bully di SMA 2 KS Cilegon yang sedang mendapatkan perhatian dari guru Bimbingan Konseling (BK) akibat perundungan verbal. Hasil penelitian menunjukkan dampak psikologis serius pada korban, termasuk penurunan rasa percaya diri, peningkatan kecemasan, gangguan tidur, kehilangan minat pada aktivitas yang disukai, dan gejala-gejala kecemasan yang berlebihan. Peran guru BK dalam memberikan dukungan emosional, layanan konseling, dan bimbingan kepada korban sangat penting. Namun, guru BK juga menghadapi tantangan, termasuk kesulitan dalam mengidentifikasi pelaku perundungan dan mengumpulkan bukti yang kuat. Respons sekolah terhadap isu perundungan juga menjadi faktor penting dalam penanganan kasus ini. Penelitian ini memberikan wawasan mendalam tentang dampak perundungan verbal pada siswa dan peran guru BK dalam membantu korban. Implikasi penelitian ini adalah pentingnya kesadaran dan langkah-langkah konkret untuk mencegah perundungan verbal dan menciptakan lingkungan sekolah yang aman dan mendukung bagi semua siswa.